2013
DOI: 10.3354/dao02613
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological assessment of the anti-salmon lice drug diflubenzuron on Atlantic cod Gadus morhua

Abstract: Increasing use of the chitin synthesis inhibitor diflubenzuron against the ectoparasitic salmon louse Lepeophtheirus salmonis in marine aquaculture has raised concerns over its environmental impacts. This study evaluated how diflubenzuron affects Atlantic cod Gadus morhua, a fish species often found near Atlantic salmon Salmo salar farms, focusing on uptake kinetics and hepatic transcriptional responses. Two experiments were conducted, one time-series trial in which the fish were given a daily dose (3 mg kg −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…In other insect species oxidases seem to play a more important role (Ishaaya, 2009), suggesting a role for cytochrome P450 enzymes. In a previous study with Atlantic cod (Gadusmorhua), diflubenzuron exposure induced CYP3A mRNA in the liver (Olsvik et al, 2013), suggesting that the cytochrome P450 system plays an important role in detoxification of benzoylurea pesticides in fish. Similar findings have been reported from murine experiments (Dubois et al, 1996;Sapone et al, 2005), with increased expression of CYP3A protein after diflubenzuron exposure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In other insect species oxidases seem to play a more important role (Ishaaya, 2009), suggesting a role for cytochrome P450 enzymes. In a previous study with Atlantic cod (Gadusmorhua), diflubenzuron exposure induced CYP3A mRNA in the liver (Olsvik et al, 2013), suggesting that the cytochrome P450 system plays an important role in detoxification of benzoylurea pesticides in fish. Similar findings have been reported from murine experiments (Dubois et al, 1996;Sapone et al, 2005), with increased expression of CYP3A protein after diflubenzuron exposure.…”
Section: Discussionmentioning
confidence: 98%
“…To control the level of infestation, the salmon farming industry uses considerable amounts of antiparasitic drugs either dissolved in water and used for bath treatment or administered orally via the feed. The increasing use of pharmaceutical drugs to control salmon lice has led to concerns about their environmental impacts (Olsvik et al, 2013;Langford et al, 2014;Samuelsen et al, 2014;Samuelsen et al, 2015;Macken et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…In two studies by Olsvik et al (2008Olsvik et al ( , 2013, the toxicology of the anti-salmon louse drugs diflubenzuron and emamectin benzoate on Atlantic cod (Gadus morhua) and Atlantic salmon (Salmo salar L.), respectively, was assessed. Three freshwater species exhibited similar sensitivities, with NOEC values of 48.7 mg/L (96 h) for rainbow trout (Oncorhynchus mykiss), 87 mg/L (96 h) for bluegill sunfish (Lepomis macrochirus) and 156 mg/L (96 h) for fathead minnow (Pinephales promelas).…”
Section: Emamectine Benzoatementioning
confidence: 99%
“…samples of muscle with skin in natural proportions (EMA, 1998;Olsvik et al, 2013). According to the documentation presented during the establishment of this MRL, the main elimination pathway in Atlantic salmon was the parent drug.…”
Section: Consumer Safetymentioning
confidence: 99%
“…Chitin synthesis inhibitors have been used as pesticides against salmon louse (Burridge et al, 2010;Denholm et al, 2002), but has lead to concerns regarding the effect of these drugs on non-target organisms. Teflubenzeron has been found in polychaetes and crustaceans in areas of aquaculture (Samuelsen et al, 2015), but was not found to be accumulated in Atlantic cod (Olsvik et al, 2013). Further knowledge regarding the molt process in salmon lice and the biological role of salmon lice chitinases can lead to improvement in the specificity of existing pesticides or development of targets for a vaccine.…”
Section: Introductionmentioning
confidence: 98%